Alternative Anesthesia of Neonatal Mice for Global rAAV Delivery in the Brain With Non-detectable Behavioral Interference in Adults - Tang, Wannan; Zillmann, Uwe; Sprengel, Rolf (Frontiers in Behavioral Neuroscience, 2020)
Viral-transduced gene expression is the current standard for cell-type-specific labeling and cell tacking in experimental neuroscience. To achieve widespread gene expression, a viral delivery method to neonatal rodents was introduced more than two decades ago. Most of those neonatal viral vector injection-based gene transduction methods in mice used deep hypothermia for anesthesia, which was reported to be associated with behavioral impairments. To explore other options for neonatal viral applications, we applied a combination of Medetomidine, Midazolam, and Fentanyl (MMF), each of which can be antagonized by a specific antagonist. Later in their adulthood, we found that adult mice, that received the MMF-induced anesthesia, combined with virus-injected into the brain at postnatal day 2, showed similar performance in all behavioral tasks tested, including tasks for motor coordination, anxiety-related tasks, and spatial memory when compared to adult naïve littermates. This demonstrates that MMF anesthesia could be safely applied to mice for neonatal viral transduction at P2.